Effect of smartphone apps on glycemic control in young patients with type 1 diabetes: A meta-analysis - Pi, Linhua; Shi, Xiajie; Wang, Zhen; Zhou, Zhiguang (Frontiers in Public Health, 2023)
Objective: Achieving glycemic control is a great challenge to young patients with type 1 diabetes (T1D), especially during the transition from childhood to adulthood. As various smartphone apps have been developed to improve glycemic control in T1D, we performed a meta-analysis of randomized controlled trials to assess the effect of smartphone apps on glycemic control in young patients with T1D. Methods: We systematically searched PubMed, Embase, and the Cochrane Library for randomized controlled trials comparing combined usual care and smartphone apps treatment to usual care alone. This meta-analysis is reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement. The primary outcomes were weighted difference in means (WMD) of HbA1c change from baseline and the person-years incidence of mild hypoglycemia or severe hypoglycemia between intervention and control groups. We assessed pooled data by use of a random-effects model. Results: Of 1190 identified studies, 9 were eligible and included in our analysis (N=748 participants). Relative to the control, using smartphone apps yielded a nonsignificant reduction in glycated hemoglobin (HbA1c) (WMD =-0.26%, 95% CI -0.56 to 0.05; P=0.10) and no increased frequency of mild hypoglycemia (WMD =1.87, 95% CI -1.52 to 5.27; P＝0.49) or severe hypoglycemia (WMD =-0.04, 95% CI -0.35 to 0.27; P＝0.80). In further subgroup analysis, compared with the recording-style app group, the auxiliary-style app group exhibited a significant reduction in HbA1c (WMD =-0.83%, 95% CI: -1.10 to -0.56, P<0.001). Conclusions: The current pooled data analysis did not reveal a significant reduction in HbA1c in young T1D patients undergoing treatment with smartphone apps and usual care in combination. However, auxiliary style apps with insulin or carbo calculators were beneficial in reducing HbA1c.